RNA-sequencing Profiles of Cell Cycle–Related Genes Upregulated during the G2-Phase in Giardia lamblia - Kim, Juri; Shin, Mee Young; Park, Soon-Jung (Korean journal of parasitology, 2019)
To identify the component(s) involved in cell cycle control in the protozoan Giardia lamblia, cells arrested at the G1/S- or G2-phase by treatment with nocodazole and aphidicolin were prepared from the synchronized cell cultures. RNA-sequencing analysis of the 2 stages of Giardia cell cycle identified several cell cycle genes that were up-regulated at the G2-phase. Transcriptome analysis of cells in 2 distinct cell cycle stages of G. lamblia confirmed previously reported components of cell cycle (PcnA, cyclin B, and CDK) and identified additional cell cycle components (NEKs, Mad2, spindle pole protein, and CDC14A). This result indicates that the cell cycle machinery operates in this protozoan, one of the earliest diverging eukaryotic lineages.